1962
DOI: 10.1136/jcp.15.5.421
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the incidence, aetiology, and pathology of senile osteoporosis

Abstract: SYNOPSIS Using previously described methods, lumbar vertebral body slabs were investigated radiologically and histologically from 300 unselected cases coming to necropsy. Calcium estimations were also made on the bones of the first 150 cases. High calcium values were mostly encountered in young adults and the calcium values tended to diminish with age, but a wide range of calcium values was still encountered in older subjects. Radiographic density of bone and calcium content tended to be higher in male than in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
1

Year Published

1967
1967
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“…Where earlier, osteoporosis was defined as an absolute decrease in the amount of bone [1][2][3] to a level below that required for mechanical support [4], later definitions added the importance of microarchitecture [5,6] and bone quality [7], a term referring to architecture, turnover, damage accumulation, and mineralization. With the changed definition of osteoporosis, the focus of investigation also changed over the years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Where earlier, osteoporosis was defined as an absolute decrease in the amount of bone [1][2][3] to a level below that required for mechanical support [4], later definitions added the importance of microarchitecture [5,6] and bone quality [7], a term referring to architecture, turnover, damage accumulation, and mineralization. With the changed definition of osteoporosis, the focus of investigation also changed over the years.…”
Section: Introductionmentioning
confidence: 99%
“…With the changed definition of osteoporosis, the focus of investigation also changed over the years. Most early studies in age-related bone changes concentrated in the description of the amount of bone volume [1][2][3][8][9][10][11][12][13][14][15][16][17], and only few investigated structural parameters such as bone surface density (BS/TV) [11,14,15], trabecular number (Tb.N) [14,18], trabecular thickness (Tb.Th) [12,14], or trabecular spacing (Tb.Sp) [12]. This was based on the intuitive idea that the mechanical properties of trabecular bone depend strongly on its apparent density or bone volume [19,20], and it became an indisputable fact that bone is lost in aging people.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have suggested that the association of osteoporosis with the menopause is largely fortuitous because autopsy studies have conclusively demonstrated that maximal bone mass is attained between ages 20 and 40 yr in both sexes, and then there is a progressive bone atrophy which begins premenopausally in women and correlates linearly with age (18)(19)(20). Clinical and in vivo densitometric studies have given conflicting results, some showing (21,22) and others failing to show (23)(24)(25) an effect of the menopause independent of age.…”
mentioning
confidence: 99%
“…All these studies show a loss of bone with age which starts earlier and is more rapid in women than men (Meema, 1962;Garn, Rhohman & Nolan, 1964;Nordin, McGregor & Smith, 1966;Smith & Rizek, 1966;Morgan et al, 1967b (Caldwell, 1962;Virtama, Gastrin & Telkka, 1962). Attempts to detect lesser degrees of biconcavity have failed or have been abandoned because of lack of precision (Smith & Rizek, 1966).…”
Section: Osteoporosismentioning
confidence: 99%